Die!Die!Die! - Kirkman, Robert 1978-; Gimple, Scott M. (Image Comics, 2019)
We don't like to admit it, but this is an evil world where evil people do evil stuff all the time. Thankfully, there is a secret cabal with the United States government that works outside our normal system to influence world matters through targeted assassination. The world around us is manipulated right under our noses, mostly for the better ... sometimes for individual gain
Keywords: Geheimbund; Einflussnahme; Manipulation; Attentat; USA; Comic